An Optimized Terpene Profile for a New Medical Cannabis Oil - Valentina Maggini; Lorenzo Calvi; Tommaso Pelagatti; Eugenia Rosaria Gallo; Celine Civati; Carlo Privitera; Flavio Squillante; Paolo Maniglia; Domenico Di Candia; Roberto Spampatti; Fabio Firenzuoli (MDPI AG, 2022)
The purpose of this analytical study was to develop an advanced formulation of medical Cannabis oil (MCO) comparing the chemical profile of different extracts obtained with two existing methods (SIFAP and CALVI) and one original upgraded (CERFIT) method. Preparation methods were applied with varying solvent, temperature, and duration of the decarboxylation and extraction steps. HPLC-MS/MS TSQ and GC/FID-HS analyses were performed to investigate cannabinoid and terpene contents in the three oil extracts. Cannabinoids profile remained comparable between the formulations. CERFIT extracts exhibited a superior quantity of total terpene hydrocarbon forms (e.g., limonene and α-pinene) with no degradation occurrence (i.e., oxidized terpenes not quantifiable). Thus, this new method optimized the phytochemical profile of the MCO presenting a value opportunity to obtain a standardized high-level therapeutic product.